(untitled) (Revista Innova Educación, 2024)
The objective of the study was to analyze the evidence on strategies for developing social-emotional skills and their impact on learning and school adjustment. A literature review was conducted of 25 scientific articles that addressed teaching strategies, programs, and theoretical approaches. The inclusion criteria were: publications in Spanish and English, empirical studies published between 2020 and 2024, that discussed strategies or programs for developing social-emotional skills in educational contexts, and that analyzed the impact of these strategies on student learning and/or school adjustment. The systematic search for studies was conducted in the databases: Scopus, Dialnet, and Google Scholar, considering the keywords “social-emotional learning,” “emotional intelligence,” “academic performance,” “school adjustment,” among others. Among the results, the studies support that the development of social-emotional skills, through teaching strategies such as social and emotional learning, positively impacts learning, school adaptation, and student well-being. These strategies strengthen key dimensions of emotional intelligence, such as self-awareness, self-management, social awareness, and relationship management. It is concluded that integrating the development of social-emotional skills into the school curriculum is relevant, through the implementation of comprehensive programs and teaching strategies that involve students, teachers, families, and communities. This contributes to the formation of more resilient students, with better self-regulation and adaptation skills, which results in more effective learning and school adjustment.